2006
DOI: 10.1128/aem.72.2.1006-1012.2006
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Kinetic Analysis of Oligofructose Consumption by Bacteroides and Bifidobacterium spp. Indicates Different Degradation Mechanisms

Abstract: The growth of pure cultures of Bacteroides thetaiotaomicron LMG 11262 and Bacteroides fragilis LMG 10263 on fructose and oligofructose was examined and compared to that of Bifidobacterium longum BB536 through in vitro laboratory fermentations. Gas chromatography (GC) analysis was used to determine the different fractions of oligofructose and their degradation during the fermentation process. Both B. thetaiotaomicron LMG 11262 and B. fragilis LMG 10263 were able to grow on oligofructose as fast as on fructose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
132
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(148 citation statements)
references
References 51 publications
11
132
0
5
Order By: Relevance
“…Although Bacteroidetes, Deinococcus-Thermus and Verrucomicrobia only made up a small proportion of bacterial sequences retrieved from the host intestines, they might play an important role in host nutrition metabolism. Bacteroidetes have been found in the intestinal microbiota of various organisms (Flint, Bayer, Rincon, Lamed & White 2008) and participate in fermentative metabolism and degradation of oligosaccharides derived from plant material (Van der Meulen, Makras, Verbrugghe, Adriany & De Vuyst 2006). DeinococcusThermus species are known for their resistance to extreme stresses, such as radiation, oxidation, desiccation and high temperature (Tian & Hua 2010), but their functional role in the gut of C. idellus deserves further research.…”
Section: H64(kf003201)mentioning
confidence: 99%
“…Although Bacteroidetes, Deinococcus-Thermus and Verrucomicrobia only made up a small proportion of bacterial sequences retrieved from the host intestines, they might play an important role in host nutrition metabolism. Bacteroidetes have been found in the intestinal microbiota of various organisms (Flint, Bayer, Rincon, Lamed & White 2008) and participate in fermentative metabolism and degradation of oligosaccharides derived from plant material (Van der Meulen, Makras, Verbrugghe, Adriany & De Vuyst 2006). DeinococcusThermus species are known for their resistance to extreme stresses, such as radiation, oxidation, desiccation and high temperature (Tian & Hua 2010), but their functional role in the gut of C. idellus deserves further research.…”
Section: H64(kf003201)mentioning
confidence: 99%
“…This limits the production of lactic acid, which results in an increase in the theoretical ratio of acetic acid to lactic acid. Moreover, degradation of inulin-type fructans increases acetic acid production at the cost of lactic acid (39,40). Detailed knowledge about the metabolism of bifidobacteria is very important because of the widespread use of these microorganisms as probiotics or as target organisms for prebiotic substrates.…”
mentioning
confidence: 99%
“…Of all the candidate prebiotics tested to date, inulin-type fructans are the most promising, and consequently, the consumption of fructans by bifidobacteria has been studied in detail both in vitro and in vivo (13,15,24,31,33,(39)(40)(41).…”
mentioning
confidence: 99%
“…Some species of the genus Bacteroides, including Bacteroides thetaiotaomicron, are known to be decomposers in the colon by fermenting carbohydrates and catabolizing polysaccharides (hemicellulose and xylan) (Falony et al, 2009;Flint, 2006;Salyers, 1995;Van der Meulen et al, 2006). Novel strains of members of the genus Bacteroides from human faeces and intestinal organs have been identified using cultureindependent techniques based on 16S rRNA gene sequence analysis (Dore et al, 1998; Eckburg et al, 2005; Gill et al, 2006;Hayashi et al, 2003;Li et al, 2009;Palmer et al, 2007) and several novel species have recently been identified and characterized (Bakir et al, 2006a, b, c;Chassard et al, 2008; Hayashi et al, 2007;Kitahara et al, 2005;Robert et al, 2007;Song et al, 2004).…”
mentioning
confidence: 99%